The categories “legal tradition” and “anomaly of the legal sphere” in the context of regulation of innovations of modern society - Чуваков, Олег Анатолійович; Чуваков, О. А.; Чуваков, Олег Анатольевич; Chuvakov, Oleh A.; Рязанов, Михайло Юрійович; Рязанов, М. Ю.; Рязанов, Михаил Юрьевич; Riazanov, Mykhailo Yu.; Ryazanov, Mykhailo; Чувакова, Ганна Михайлівна; Чувакова, Г. М.; Чувакова, Анна Михайловна; et al. (Universidad de la Amazonia, 2020)
The relevance of the article is due to ignorance of legal traditions and lack of sufficient theoretical and practical basis for legal inheritance make it impossible to complete the formation of a coherent and stable legal system since it is based not so much on borrowing but on one's own legal experience as is built on centuries-old legal traditions as well as modern achievements of legal realities. The object of the study is public relations that cannot be settled through standard means of regulation. The article deals with the categories "legal tradition" and "anomaly of the legal sphere". The method of comparison, the dialectical method, the logical method, the method of analysis and the method of synthesis, the method of deduction in the writing of this scientific work were used. As a result of the study, the authors made the following conclusions. To normalize the anomalies of the legal sphere and accelerate their adaptation in the legal field, the legislative nature of such an anomaly should first of all be determined, as well as to fill the gaps in its legal regulation, which will result in a reduction of conflict situations, respect for human rights and interests, further formation of a new legal tradition and an increase in legal heritage.

Актуальність статті зумовлена необізнаністю у власних правових традиціях та відсутністю достатньої теоретичної та практичної бази щодо правової спадщини, що зумовлює неможливість завершення формування цілісної та стійкої правової системи, оскільки її основу складають не стільки запозичення, скільки власний правовий досвід, що будується на столітніх правових традиціях та звичаях, а також на сучасних надбаннях правових реалій. Об’єктом дослідження є суспільні відносини, що не можуть бути врегульовані за допомогою типових засобів регулювання. Предметом дослідження в статті є безпосередньо категорії "правова традиція" та "аномалія правової сфери". Були використані метод порівняння, діалектичний метод, логічний метод, метод аналізу та метод синтезу, метод дедукції при написанні даної наукової роботи. У результаті проведеного дослідження автори зробили наступні висновки. Для унормування аномалій правової сфери та пришвидшення їх адаптації у правовому полі слід в першу чергу визначити законодавчо правову природу такої аномалії, а також заповнити прогалини у її правовому регулюванні, що матиме наслідком зменшення конфліктних ситуацій, дотримання прав і інтересів людини, подальше формування нової правової традиції та примноження правової спадщини.

Актуальность статьи обусловлена ​​незнанием собственных правовых традиций и отсутствием достаточной теоретической и практической базы для правового наследия, что приводит к невозможности завершения формирования целостной и устойчивой правовой системы, поскольку ее основу составляют не столько заимствование, сколько собственный правовой опыт, что строится на столетних правовых традициях и обычаях, а также на современных достижениях правовых реалий. Объектом исследования являются общественные отношения, которые не могут быть урегулированы с помощью обычных мер регулирования. Предметом исследования в статье является непосредственно категории "правовая традиция" и "аномалия правовой сферы". Были использованы метод сравнения, диалектический метод, логический метод, метод анализа и метод синтеза, метод дедукции при написании данной научной работы. В результате проведенного исследования авторы сделали следующие выводы. Для унормирования аномалий правовой сферы и ускорения их адаптации в правовом поле следует в первую очередь определить законодательно правовую природу такой аномалии, а также заполнить пробелы в ее правовом регулировании, что приведет к уменьшению конфликтных ситуаций, соблюдению прав и интересов человека, дальнейшему формированию новой правовой традиции и приумножению правового наследия.
Chuvakov O. The categories “legal tradition” and “anomaly of the legal sphere” in the context of regulation of innovations of modern society / O. Chuvakov, M. Ryazanov, H. Chuvakova, T. Pavlova // Amazonia Investiga. – V. 9 (25). – Universidad de la Amazonia, 2020. – P. 411-417.
Keywords: legal tradition; legal anomaly; legal regulation; legal inheritance; domain name; правова традиція; аномалія правової сфери; правове регулювання; правова спадщина; домене ім’я; правовая традиция; аномалия правовой сферы; правовое регулирование; правовое наследие; доменное имя; Research Subject Categories::LAW/JURISPRUDENCE